Characterizing food environments in Central Uganda - Namatovu, Jane; Achandi, Esther Leah; Omosa, Esther; Ahumuza, Ronnie; Dominguez, Paula; Ouma, Emily A. (International Livestock Research Institute, 2025)
This report focuses on findings from 16 focus group discussions with adult men and women from four districts in Central region of Uganda to better understand the different types of food environments that the communities have access to, and the types of foods they access, how the various foods are acquired and how the food access points have changed across seasons and time.